Curative to palliative care transition challenges in the intensive care unit. A narrative review. - Koutsouki, Sotiria; Kosmidis, Dimitrios (Health & Research Journal, 2023)
Abstract Introduction: The need for high quality palliative care services for critically ill patients and their families remains of high importance. Purpose: This review aims to present the benefits and barriers to implementing palliative care in Intensive Care Units and suggest ways to facilitate the shift from therapeutic to palliative care. Methods: PubMed, Scopus, and Google Scholar databases were searched online. Studies included were eligible for the provision of palliative care in the intensive care unit, published in English from 2012 through 2022. Review: Evidence shows that integrating palliative care impacts the quality of life in intensive care unit and increases rates of use of palliative care facilities. On the other hand decrease length of stay and impacts the cost and the opportunity cost of the intensive care unit. The data suggest that a large subset of intensive care units patients would benefit from palliative care, but palliative care remains underutilized in the ICU setting. Lack of training in palliative care, organizational factors, decisions about end of life, lack of defined criteria for inclusion, and life-saving culture of the intensive care unit are barriers to providing palliative care. Efforts should focus on education, support for effective communication and decision-making, early integration of a palliative approach, redesign of clinical protocols, and reallocation of resources to provide an environment conducive to quality at the end of life. Conclusion: Involving palliative care in critically ill patients has reduced intensive care unit resource use. Nurses need to define their essential management roles within the multidisciplinary critical care team and help develop systems by which these roles can be implemented.